Concise Review: Stem Cells in Pancreatic Cancer: From Concept to Translation. (14th August 2015) - Raj, Deepak; Aicher, Alexandra; Heeschen, Christopher
Abstract Pancreatic cancer stem cells (CSCs) have been first described in 2007 and since then have emerged as an intriguing entity of cancer cells with distinct functional features including self‐renewal and exclusive in vivo tumorigenicity. The heterogeneous pancreatic CSC pool has been implicated in tumor propagation as well as metastatic spread. Clinically, the most important feature of CSCs is their strong resistance to standard chemotherapy, which results in fast disease relapse, even with today's more advanced chemotherapeutic regimens. Therefore, novel therapeutic strategies to most efficiently target pancreatic CSCs are being developed and their careful clinical translation should provide new avenues to eradicate this deadly disease. Stem Cells2015;33:2893—2902